Peningkatan Literasi Keuangan dan Pelatihan Bahasa Inggris Sejak Dini Bagi Siswa SD Kanisius Mlese - Maria Rosa Kumala Dewi; Kristantiningtyas, Dhian; Pratama, Sangaji Yudhi; Rondonuwu, Victor (Universitas Sahid Surakarta, 2024)
This community service activity aims to provide an understanding of financial literacy from an early age. Apart from that, this service also provides brief English language training. The habit of saving will teach students to learn to be independent and practice not relying on their parents from an early age. The English language training in this service focuses on speaking regarding the introduction. The partner in this service activity is Kanisius Mlese Elementary School, located in Klaten Regency. The service team consists of two lecturers from the D3 Accounting study program, one from the D3 English language study program, and one from the Bachelor of Information Systems study program. The service participants are students from grades three to six. This service is carried out by providing explanations and training directly to students. Hopefully, this dedication can increase students' interest in saving from an early age. Apart from that, students are also expected to be able to introduce themselves using English properly and correctly.